An efficient reusable perylene hydrogel for removing some toxic dyes from contaminated water. Issue 9 (3rd February 2021) - Abdulwahid, Ali A; Alwattar, Aula A; Haddad, Athir; Alshareef, Mubark; Moore, Joshua; Yeates, Stephen G; Quayle, Peter
Abstract: The synthesis of adsorbents that meet the need for large‐scale production at relatively low cost and are capable of removing anionic and cationic toxic dyes from aqueous solutions, with high sorption capacity and reusability, is urgently needed from an environmental and industrial viewpoint. In this context the identification of hydrogels that remove dyes efficiently under ambient conditions and at near‐neutral pH without the necessity of pre‐treatment is an imperative. In this study we report the preparation of two hydrogels using the redox polymerisation of acrylamide, hydroxyethylmethacrylate (HEMA) and N ‐isopropylacrylamide (H1 ) and acrylamide, HEMA, N ‐isopropylacrylamide and perylene‐5‐ylpent‐3‐yne‐2‐methylprop‐2‐enoate‐ co ‐2‐methyl‐2‐(prop‐2‐enoylamino)propane‐1‐sulfonic acid (PePnUMA‐ co ‐AMPS) (H2 ). These hydrogels proved to be effective for the removal of methylene blue (MB), fuchsin acid (FA) and Congo Red (CR) from aqueous solution at near‐neutral pH where their adsorption behaviour was in keeping with the Langmuir model having q max values of 769.2 mg g −1 (MB), 1666.7 mg g −1 (FA) and 2358.2 mg g −1 (CR). The adsorption of MB and FA by these hydrogels follows pseudo‐first‐order kinetics, whilst the adsorption of CR follows pseudo‐second‐order kinetics. Detailed thermodynamic analysis indicated that the dye–adsorbent interaction is primarily one of physisorption in nature. Finally, desorption studies carried out in 1.0 mol L –1 NaClO4 indicated that these adsorbents could be recycled at least four times using a variety of dyes while maintaining their mechanical properties. © 2021 The Authors. Polymer International published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : A readily available low‐cost hydrogel was used for the removal of toxic dyes from aqueous solution. This adsorbent showed enhanced adsorption capacity and excellent regeneration efficiency over four successive adsorption cycles.